Revealing the Absence of Microbiota in Hypertrophic Mucosa of Inferior Turbinate - Rangga Putra Nugraha; Asti Widuri; Luh Putu Lusy Indrawati; Budi Yuli Setianto; Mahyarudin Mahyarudin; Mardhia Mardhia; Delima Fajar Liana (International Journal of Biomedicine)
Background: Nasal congestion is the most common symptom presented in daily clinical practice, and inferior turbinate hypertrophy (ITH) is the most frequent cause. However, histopathological analysis of turbinate hypertrophy remains unclear. Therefore, this study aimed to assess the presence of microbiota in the mucosa of ITH, to clarify the role in nonspecific immune responses. Methods and Results: This prospective and cross-sectional study evaluated microbiota in hypertrophic inferior turbinate mucosa. A total of 42 patients and specimens of ITH were enrolled during the endoscopic submucosal rhinoplasty. Intraoperative specimens were collected and inserted into DNA/RNA protectors.The specimens were subjected to DNA extraction, which was followed by PCR electrophoresis. The results showed that metagenomic examination was needed to assess microbiota diversity in tissue, including electrophoresis and sequencing of PCR-amplified DNA such as 16S rRNA in the inferior concha mucosa and the preservation fluid. In this examination, no bands were found at the 1500 bp marker, showing that no bacterial 16S gene fragments were present in either tissue specimen or preservation fluid. Conclusion: Microbiota were found only in mucus or the nasal mucosa lining and not in the tissue. The results further emphasized the position and role of microbiota as a physiological nonspecific immune response, providing a basis for further studies in learning about microbiota of the respiratory tract, specifically the nasal cavity.